New insights into the evolution and functional divergence of the CIPK gene family in Saccharum - Su, Weihua (BMC Genomics, 2020)
BACKGROUND: Calcineurin B-like protein (CBL)-interacting protein kinases (CIPKs) are the primary components of calcium sensors, and play crucial roles in plant developmental processes, hormone signaling transduction, and in the response to exogenous stresses. RESULTS: In this study, 48 CIPK genes (SsCIPKs) were identified from the genome of Saccharum spontaneum. Phylogenetic reconstruction suggested that the SsCIPK gene family may have undergone six gene duplication events from the last common ancestor (LCA) of SsCIPKs. Whole-genome duplications (WGDs) served as the driving force for the amplification of SsCIPKs. The Nonsynonymous to synonymous substitution ratio (Ka/Ks) analysis showed that the duplicated genes were possibly under strong purifying selection pressure. The divergence time of these duplicated genes had an average duplication time of approximately 35.66 Mya, suggesting that these duplication events occurred after the divergence of the monocots and eudicots (165 Mya). The evolution of gene structure analysis showed that the SsCIPK family genes may involve intron losses. Ten ScCIPK genes were amplified from sugarcane (Saccharum spp. hybrids). The results of real-time quantitative polymerase chain reaction (qRT-PCR) demonstrated that these ten ScCIPK genes had different expression patterns under abscisic acid (ABA), polyethylene glycol (PEG), and sodium chloride (NaCl) stresses. Prokaryotic expression implied that the recombinant proteins of ScCIPK3, − 15 and − 17 could only slightly enhance growth under salinity stress conditions, but the ScCIPK21 did not. Transient N. benthamiana plants overexpressing ScCIPKs demonstrated that the ScCIPK genes were involved in responding to external stressors through the ethylene synthesis pathway as well as to bacterial infections. CONCLUSIONS: In generally, a comprehensive genome-wide analysis of evolutionary relationship, gene structure, motif composition, and gene duplications of SsCIPK family genes were performed in S. spontaneum. The functional study of expression patterns in sugarcane and allogenic expressions in E. coli and N. benthamiana showed that ScCIPKs played various roles in response to different stresses. Thus, these results improve our understanding of the evolution of the CIPK gene family in sugarcane as well as provide a basis for in-depth functional studies of CIPK genes in sugarcane. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-020-07264-9.